A Computed Tomography-Based Morphometric Assessment of the Foramen Lacerum in a Turkish Population Using the 3D Slicer Method - Merve Muslu; Ömür Karaca; Aybars Kökçe; Niyazi Acer (Medicina)
Background and Objectives: The foramen lacerum (FL), located at the base of the skull, is generally considered the safest anatomical pathway for accessing the internal carotid artery (ICA) and the vidian canal (VC) during surgical procedures. We aimed to evaluate the morphometric characteristics of FL, VC, and related structures. Materials and Methods: This study utilized cranial computed tomography (CT) images obtained between 2016 and 2018 at Balıkesir University Faculty of Medicine for various clinical indications. A retrospective analysis was performed on cranial CT images from 77 patients, comprising 42 females and 35 males. The length and width of the FL, the length of the VC, and the angles formed between the VC and the pterygosphenoidal fissure and between the VC and the palatovaginal canal were measured. All measurements were performed using the three-dimensional (3D) Slicer software to ensure precision and consistency. Results: Males had significantly longer right and left FL lengths and left FL width than females (p < 0.05). No significant gender-based differences were found in VC length on either side. The angle between the VC and the pterygosphenoidal fissure was significantly larger in males (p < 0.05). Additionally, increased FL length and width were significantly correlated with larger angles between the VC and the pterygosphenoidal fissure in all subjects (p < 0.05). The anatomical variations of the FL Type 1 (normal) were identified as the most prevalent configuration across the study population. Type 2 (canal-shaped) ranked as the second most frequent variant in females, whereas Type 3 (bridged) was the second most commonly observed form in males. Conclusions: Preoperative identification of FL anatomical variations, which differ between individuals and sexes, may enhance the safety of skull base surgeries and minimize postoperative complications. The morphometric data presented in this study provide valuable guidance for clinicians planning interventions involving the FL and surrounding structures, and contribute valuable insights to anatomists regarding regional morphology.